Harakah dan Kemandirian Perempuan - Muhammad Mukhtar (LPPM IAIN Parepare, 2019)
Women have equal access to men in their role in society. The macro context, which is entirely different, has an impact on the problem of the interpretation of the Koran as a whole and specifically concerning the harakah and independence of women. The Koran does not say that all men have more advantages than all women. But the Koran says